2016
DOI: 10.1021/acs.jafc.6b00108
|View full text |Cite
|
Sign up to set email alerts
|

Fermented Goat’s Milk Consumption Improves Duodenal Expression of Iron Homeostasis Genes during Anemia Recovery

Abstract: Despite the crucial roles of duodenal cytochrome b (Dcytb), divalent metal transporter 1 (DMT1), ferritin light chain (Ftl1), ferroportin 1 (FPN1), transferrin receptor 1 (TfR1), and hepcidin antimicrobial peptide (Hamp) in Fe metabolism, no studies have investigated the modulations of these genes during Fe repletion with fermented milks. Analysis included Fe status markers and gene and protein expression in enterocytes of control and anemic animals fed fermented milks. Fermented goat's milk up-regulated enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 33 publications
2
28
0
1
Order By: Relevance
“…In this study, a decrease in serum hepcidin was recorded in animals consuming fermented goat milk, and our research group have also previously reported 15 that hepcidin duodenal expression was found to be decreased in rats consuming fermented goat milk in comparison with rats consuming cow milk. This downregulation of hepcidin would increase Fe efflux from the duodenal cells, because this correlates inversely with the activity of ferroportin and Fe absorption, improving hematological parameters and promoting anemia recovery.…”
Section: Resultssupporting
confidence: 70%
See 4 more Smart Citations
“…In this study, a decrease in serum hepcidin was recorded in animals consuming fermented goat milk, and our research group have also previously reported 15 that hepcidin duodenal expression was found to be decreased in rats consuming fermented goat milk in comparison with rats consuming cow milk. This downregulation of hepcidin would increase Fe efflux from the duodenal cells, because this correlates inversely with the activity of ferroportin and Fe absorption, improving hematological parameters and promoting anemia recovery.…”
Section: Resultssupporting
confidence: 70%
“…Cardiac Fe‐deficiency is present in patients with heart failure and is associated with impaired mitochondrial function, abnormal sarcomere structure, and left ventricular systolic dysfunction; however, in our study, after supplying the fermented milk diets, the hematological parameters recovered, revealing that Fe deficiency was recovered and therefore most of the parameters related to CD were unaffected at the end of the EP. However, CTGF and MCP‐1 were still increased in anemic animals fed fermented cow milk either with normal‐Fe or Fe‐overload, and VEGF was also higher in anemic animals fed fermented goat or cow milk with Fe‐overload, revealing that, although hematological status was normal, Fe homeostasis and metabolism recovered better with fermented goat milk, as previously described . Fermented goat milk upregulates enterocyte duodenal cytochrome b, divalent metal transporter 1, ferritin, and ferroportin 1 and downregulates transferrin receptor 1 and hepcidin antimicrobial peptide, improving Fe homeostasis and storage in erythropoietic and target organs and avoiding vascular damage due to Fe deficiency or overload.…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations